Analysis Of Price, Promotion And Location Of Purchasing Decisions At PT Samera Propertindo - Jesslyn Wong; Muhammad Agung Anggoro; Andrew Pranata Sinaga; Dandy Irawan (Institute of Computer Science (IOCS), 2021)
This study aims to examine and analyze the effect of Price Quality, Promotion and Location on Purchasing Decisions at PT Samera Propertindo. The research method uses quantitative. The population was 196 consumers and the sample was 137 consumers. The sampling technique used was random sampling. The results of the calculation of hypothesis testing partially and simultaneously Price, Promotion and Location simultaneously have a positive and significant effect on Purchasing Decisions at PT Samera Propertindo..